Microglia Dynamics and Interactions with Motoneurons Axotomized After Nerve Injuries Revealed By Two-Photon Imaging - Travis M. Rotterman (Nature Portfolio, 2020)
Abstract The significance of activated microglia around motoneurons axotomized after nerve injuries has been intensely debated. In particular, whether microglia become phagocytic is controversial. To resolve these issues we directly observed microglia behaviors with two-photon microscopy in ex vivo spinal cord slices from CX3CR1-GFP mice complemented with confocal analyses of CD68 protein. Axotomized motoneurons were retrogradely-labeled from muscle before nerve injuries. Microglia behaviors close to axotomized motoneurons greatly differ from those within uninjured motor pools. They develop a phagocytic phenotype as early as 3 days after injury, characterized by frequent phagocytic cups, high phagosome content and CD68 upregulation. Interactions between microglia and motoneurons changed with time after axotomy. Microglia first extend processes that end in phagocytic cups at the motoneuron surface, then they closely attach to the motoneuron while extending filopodia over the cell body. Confocal 3D analyses revealed increased microglia coverage of the motoneuron cell body surface with time after injury and the presence of CD68 granules in microglia surfaces opposed to motoneurons. Some microglia formed macroclusters associated with dying motoneurons. Microglia in these clusters display the highest CD68 expression and associate with cytotoxic T-cells. These observations are discussed in relation to current theories on microglia function around axotomized motoneurons.